Effect of a treat-to-target strategy based on methotrexate and intra-articular betamethasone with or without additional cyclosporin on MRI-assessed synovitis, osteitis, tenosynovitis, bone erosion, and joint space narrowing in early rheumatoid arthritis: results from a 2-year randomized double-blind placebo-controlled trial (CIMESTRA). (3rd September 2017) - Møller-Bisgaard, S; Ejbjerg, BJ; Eshed, I; Hørslev-Petersen, K; Hetland, ML; Jurik, AG; Thomsen, H; Torfing, T; Stengaard-Pedersen, K; Junker, P; Krogh, NS; Lottenburger, T; et al.
Abstract : Objectives : To investigate whether a treat-to-target strategy based on methotrexate (MTX) and intra-articular (IA) betamethasone suppresses magnetic resonance imaging (MRI)-determined measures of disease activity and reduces joint destruction in early rheumatoid arthritis (eRA) patients, and to investigate whether concomitant cyclosporin A (CyA) provides an additional effect. Method : In the 2-year randomized, double-blind, treat-to-target trial CIMESTRA, 160 patients with eRA (< 6 months) were randomized to MTX, intra-articular betamethasone and CyA, or placebo CyA. A total of 129 patients participated in the MRI substudy, and had contrast-enhanced MR images of the non-dominant hand at months 0, 6, 12, and 24. MR images were evaluated for osteitis, synovitis, tenosynovitis, bone erosion, and joint space narrowing (JSN), using validated scoring methods. Results : Significant reductions were seen at 6 months in all inflammatory parameters [synovitis, mean change –1.6 (p < 0.001, Wilcoxon), tenosynovitis, –3.5 (p < 0.001), and osteitis, –1.3 (p < 0.05)] and at 12/24 months in synovitis and tenosynovitis [–1.6/–2.2 and –3.6/–3.8, respectively; all p < 0.001]. MRI signs of inflammation were not fully eliminated, and increases in erosion and JSN scores were observed at 6 months [0.4 (p < 0.01)/0.1 (p < 0.05)], 12 months [0.8 (p < 0.001)/0.3 (p < 0.01)], and 24 months [1.0 (p < 0.001)/0.4 (p < 0.001)]. Clinical measures decreased significantly (p < 0.001) at all time points. There were no consistent statistically significant differences between treatment groups. Conclusions : In this eRA treat-to-target trial, MTX and intra-articular glucocorticoids markedly reduced, but did not eliminate, MRI osteitis, synovitis, and tenosynovitis. Accordingly, minimal but statistically significant increases in bone erosion and JSN were observed. No additional effect of CyA was demonstrated.